Arched snap motor: power flow analysis. (17th September 2021) - Misu, Kenji; Mochiyama, Hiromi
Abstract : Impulse force is effective for purposes such as system analysis, mobile robots, and haptic devices. However, the most popular DC motor actuator is not suitable for generating an impulse force. Thus, the lack of a compact impulse force generator has become a problem. We propose a snap motor that is a compact and rapid impulse force generator. In this paper, we propose a slider mechanism for the arched snap motor to increase the durability of the frame. This paper shows a reasonable explanation the function of the slider mechanism on an arched snap motor with simulation. Then, experiments showed that the energy conversion efficiency of the input electric energy to the buckling energy is about 60%. This paper provides a design method for a simple and compact impulse force generator. GRAPHICAL ABSTRACT: UF0001